2005
DOI: 10.1530/rep.1.00535
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in blastocyst implantation in the rhesus monkey

Abstract: Successful blastocyst implantation depends on the interaction between cells of maternal endometrium and conceptus, as well as adequate blood supply to the site of blastocyst implantation. Nitric oxide (NO) generally plays a significant role in the local regulation of vascular physiology in a variety of mammalian tissue systems, however, its role in blastocyst implantation and placentation in the primate is not known. The aim of the present study was to examine: (i) NADH-diaphorase activity and expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…Likewise, iNOS expression in human endometrial stromal cells can be enhanced by IL-1β and IFN-γ [40]. These cytokines, including IFN-γ and IFN-ω in rabbits [41], are considered to be engaged in the implantation-recognition process by advancing embryo infiltration and tissue remodeling of the endometrium via effects of NO and matrix metalloproteinase [18]. It seemed that induction of NOS isoenzymes is an underlying event in the developing placenta in the postimplantation period for initiation and reconstruction of placental vascular systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, iNOS expression in human endometrial stromal cells can be enhanced by IL-1β and IFN-γ [40]. These cytokines, including IFN-γ and IFN-ω in rabbits [41], are considered to be engaged in the implantation-recognition process by advancing embryo infiltration and tissue remodeling of the endometrium via effects of NO and matrix metalloproteinase [18]. It seemed that induction of NOS isoenzymes is an underlying event in the developing placenta in the postimplantation period for initiation and reconstruction of placental vascular systems.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of rabbit pregnancy, vascular remodeling in the maternal and fetal vessels becomes dominant, as shown by the narrowing intervillous spaces and drastic ramifications in the labyrinth. Recent studies in various mammalian species indicate that NO acts as a major modulator of uterine blood flow during pregnacy [13], placental-fetal blood flow [14] and placental angiogenesis [2].The distribution of iNOS and eNOS has been confirmed in the placentas of many animal species including the human [15], rat [16], sheep [3,17] and rhesus monkey [18]. In spite of the fact that the rabbit is a useful research model in the field of reproductive and developmental biology, previous published literature is absolutely silent about the assessment of iNOS and eNOS in the rabbit placenta.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The embryo implantation is unsuccessful with blocking NO production. The studies have shown that great amounts of NO and NOS might play a role in the pathogenesis of endometriosis (Wu et al, 2003), and NO might play an important role in the establishment of pregnancy in the rhesus monkey (Sengupta et al, 2005). NO production was increased in LPS-induced embryonic resorption mice, mainly due to the induction of expression of inducible nitric oxide synthase (iNOS) isoform in the decidua and uterus, and neuronal nitric oxide synthase (nNOS) isoform in the decidua (Ogando et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Using NADPH diaphorase staining, NOS activity has been reported to be higher in the inner cell mass (ICM) than in the trophectoderm in mouse (Nishikimi et al. 2001) and monkey blastocysts (Sengupta et al. 2005).…”
Section: Primers Used For Rt‐pcr Amplificationmentioning
confidence: 99%